2004
DOI: 10.1023/b:jopr.0000017223.98667.10
|View full text |Cite
|
Sign up to set email alerts
|

Who Do You Love, Your Mother or Your Horse? An Event-Related Brain Potential Analysis of Tone Processing in Mandarin Chinese

Abstract: In Mandarin Chinese, word meaning is partially determined by lexical tone (Wang, 1973). Previous studies suggest that lexical tone is processed as linguistic information and not as pure tonal information (Gandour, 1998; Van Lanker & Fromkin, 1973). The current study explored the online processing of lexical tones. Event-related potentials were obtained from 25 Mandarin speakers while they listened to normal and anomalous sentences containing one of three types of semantic anomalies created by manipulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 30 publications
4
40
1
Order By: Relevance
“…We would therefore argue that both children and adults were able to efficiently use tonal information to constrain word recognition as soon as it became available. This conclusion is further motivated by previous work, including our own, highlighting the pivotal role of tone in Mandarin spoken word recognition (Brown-Schmidt & Canseco-Gonzalez, 2004; Malins & Joanisse, 2010; Zhao et al, 2011; Malins & Joanisse, 2012). The current study adds to the existing literature by suggesting that tonal processing systems are sufficiently developed in ten-year old children such that they resolve tonal competition over a similar time course as adults.…”
Section: Discussionsupporting
confidence: 56%
“…We would therefore argue that both children and adults were able to efficiently use tonal information to constrain word recognition as soon as it became available. This conclusion is further motivated by previous work, including our own, highlighting the pivotal role of tone in Mandarin spoken word recognition (Brown-Schmidt & Canseco-Gonzalez, 2004; Malins & Joanisse, 2010; Zhao et al, 2011; Malins & Joanisse, 2012). The current study adds to the existing literature by suggesting that tonal processing systems are sufficiently developed in ten-year old children such that they resolve tonal competition over a similar time course as adults.…”
Section: Discussionsupporting
confidence: 56%
“…Evidences of the linguistic nature of lexical tone processing have been also found by Brown-Schmidt and Canseco-Gonzalez (2004): they showed that N400, the event-related potential component typically elicited by unexpected linguistic stimuli, is also present in Mandarin speakers when the semantic alteration is determined by the lexical tone.…”
Section: Introductionmentioning
confidence: 53%
“…Previous studies suggest that lexical tones are processed as linguistic information and not as a pure tonal information (Brown-Schmidt and Canseco-Gonzalez 2004;Klein et al 2001;Van Lancker and Fromkin 1973;Wang et al 1999). The problem of the double linguistic-tonal nature of lexical tones has been extensively faced taking into account the brain lateralization of cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the role of tone and segmental information in Cantonese word processing (Schirmer et al 2005), the time course and amplitude of the N400 effect, a negativity that is associated with processing the semantic meaning of a word, were comparable for tone and segmental violations (cf. Brown-Schmidt & Canseco-Gonzalez 2004). The MMN, a cortical potential elicited by an odd-ball paradigm, reflects preattentive processing of auditory stimuli.…”
Section: Evidence That Knowledge Of Tonal Categories May Influence Eamentioning
confidence: 99%